2006
DOI: 10.1088/0741-3335/48/11/007
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of number density and size distribution of dust in DIII-D during normal plasma operation

Abstract: Dust particles with submicron radii have been observed in the scrape-off layer (SOL) and divertor region of DIII-D during normal plasma operation. The particles are observed via their relatively large cross section for Rayleigh scattering of the Nd : YAG laser used for Thomson scattering measurements of electron density and temperature. In the outer region of the SOL particles are rare, with an average density of about 6 × 10 3 particles m −3 . The particle density falls sharply going toward the last closed fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 17 publications
(33 reference statements)
3
45
0
Order By: Relevance
“…1c) due to dust ablation in TEXTOR plasmas. The evaluation of dust concentration immediately after dust mobilization provided a value of 0.5 particle/cm 3 which is about 100 times higher than that measured for intrinsic dust in DIII-D [19].…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…1c) due to dust ablation in TEXTOR plasmas. The evaluation of dust concentration immediately after dust mobilization provided a value of 0.5 particle/cm 3 which is about 100 times higher than that measured for intrinsic dust in DIII-D [19].…”
mentioning
confidence: 60%
“…An additional, smaller 6 intensity launch occurred during the start of NBI, due to further increase of the plasma load. The usual amount of mobilized impurities was about 5×10 19 atoms, the maximum amount did not exceed 1.6×10 21 atoms.…”
Section: Mobilization Of Dust In Textor Plasmamentioning
confidence: 86%
“…Dust particles in tokamaks were first detected by a standard TS diagnostics with the use of Mie scattering [11]. Possibilities of such diagnostic are restricted by (1) a very high intensity of laser probing beams which burns small particles out before they have been detected, (2) a short laser pulse duration and small probing volume which reduces the sensitivity and detection probability of dust particles Mie scattering at the laser probing wavelength causes the diagnostic to be affected by stray light.…”
Section: Pos(ecpd2015)034mentioning
confidence: 99%
“…The machine is outfitted with advanced plasma diagnostics including a Thomson scattering system based on 8 ND:YAG lasers and used primarily for the measurements of the electron density and temperature profiles. Spectrally nonshifted detector channels allow for detection of dust particles via Mie scattering [6,7]. The diagnostic can resolve the size of small particles between 50-250 nm in diameter.…”
Section: Measurements Of Naturally Occurring Dustmentioning
confidence: 99%
“…Nevertheless, statistical analysis of the data provides an estimate of the total dust content in the edge and scrape-off layer (SOL) plasmas and allows establishing trends in the dust production rates. It has been shown that during normal plasma operations in DIII-D dust is not a major impurity source, with total carbon content of the dust being less than a few percent of the plasma carbon impurity content [6]. Statistical evidence points to increased dust production in discharges with edge localized modes (ELMs) and disruptions.…”
Section: Measurements Of Naturally Occurring Dustmentioning
confidence: 99%